Pemaknaan Publik terhadap Perilaku Flexing oleh Pemilik Merek Skincare Lokal dalam Perspektif Literasi Digital - Amanda, Novia; Athaya, Nabila Dewi; Boer, Rino Febrianno (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyze how audiences interpret the flexing content of a local skincare brand owner and the role of digital literacy in this process. Using a qualitative netnographic approach, data was obtained through analysis of the brand owner's TikTok content and in-depth interviews with four informants who are both audience members and consumers. The results show that flexing as a symbolic branding strategy is interpreted in various ways, ranging from admiration to suspicion. Digital literacy plays a crucial role in filtering information, assessing content credibility, and influencing purchasing decisions. The contrasting reactions in netizen comments confirm that digital literacy levels determine how society, particularly the lower-middle class, forms perceptions of flexing practices on social media.